POLA RUANG IBUKOTA KECAMATAN JABIREN RAYA KABUPATEN PULANG PISAU - Amiany (Jurusan Arsitektur UPR, 2017)
Problems in urban planning that always continue from time to time will stumble on community behavior that arises outside of government planning. Revealing the plurality of urban problems, causing the emergence of causes to increase the need for space, facilities and infrastructure.Pulang Pisau District is one of the newly developed regencies which has experienced a fairly high development, one of which is the geographical condition of Jabiren Raya Sub-District located on the axis of Pulang Pisau City - Palangka Raya City is developing along with other sub-districts, especially in functional areas. The residents of Jabiren Raya Subdistrict tend to have more interaction with the City of Palangka Raya considering that the city of Palangka Raya is closer and quite complete to the needs of the community. While other linkages with cities outside the Regency are Jabiren As a transit point for good population movements from Banjarmasin, Kuala Kapuas and from other regions in Central Kalimantan. The potential development of Jabiren City is the availability of large enough vacant land supported by a fairly strategic location in the eastern part of Pulang Pisau district where it can be a gateway for community movements and goods from neighboring districts.The availability of this vast vacant land provides a considerable opportunity to determine policies and oversee regional development and reduce conflicts due to difficulties in regulating land use. Community development in the Capital District of Jabiren Raya District has customs and daily habits, so it should be noted also in the development of the Capital District.